Antireflux stents to reduce the risk of cholangitis in patients with malignant biliary strictures: a randomized trial - Hu, Bing; Wang, Tian-tian; Wu, Jun; Shi, Zhi-mei; Gao, Dao-jian; Pan, Ya-min (Endoscopy, 2014)
Background and study aims: There are limited data on the role of antireflux biliary stents. This single-center randomized trial compared the endoscopic use of partly covered antireflux metal stents (pcARMS) with that of standard uncovered self-expandable metal stents (ucSEMS) for the palliation of nonhilar malignant biliary obstruction. Patients and methods: Between August 2007 and February 2012, patients with nonhilar malignant biliary obstruction were randomly assigned to treatment with either pcARMS or ucSEMS. Subsequent follow-up was conducted in clinic or by phone. The primary outcome was onset of cholangitis within 12 months of stenting. Secondary outcomes included other morbidities, stent dysfunctions, and survival. Results: Altogether 112 patients were included, 56 in each group. The stents were successfully deployed in all patients. Satisfactory jaundice control was achieved in 49 cases in the pcARMS group, compared with 47 in the ucSEMS group (P = 0.135). Fewer patients experienced cholangitis in the pcARMS group than in the ucSEMS group (10 vs. 21 patients; P = 0.035), and the frequency of episodes was less (P = 0.022). Respectively, 17 and 29 stent dysfunctions before death were observed in the pcARMS and ucSEMS groups (P = 0.051) and the median stent patency was 13.0 (standard deviation [SD] 3.4) and 10.0 (1.2) months, respectively (P = 0.044). At final follow-up, in January 2013, 50 /52 and 52 /55 patients had died and no difference in median survival was seen between the two groups (8.0 vs. 9.0 months, P = 0.56). Conclusions: Stenting with pcARMS compared with standard ucSEMS reduces risk of ascending cholangitis and has longer stent patency, but does not increase patient survival. Chictr.org. number, ChiCTR-TRC-11001800.